"Normal" Creatinine Levels Predict Persistent Kidney Injury and Waitlist Mortality in Outpatients With Cirrhosis. Issue 5 (10th July 2018) - Cullaro, Giuseppe; Park, Meyeon; Lai, Jennifer C.
Abstract : Acute kidney injury (AKI) is a critical determinant of outcomes in hospitalized patients with cirrhosis, but little is known of the impact of AKI in the outpatient setting. We analyzed 385 adult outpatients with cirrhosis listed for liver transplant at a single center; excluded were those with severe hepatic encephalopathy, with hepatocellular carcinoma, or on hemodialysis. Baseline serum creatinine (bCr) was defined as the lowest value recorded, peak Cr as the highest value, ΔCr as peak Cr minus bCr, AKI as a rise in serum Cr (sCr) by ≥0.3 mg/dL from bCr, persistent kidney injury as elevation of sCR by ≥0.3 mg/dL from bCr on each subsequent clinical assessment. Among 385 outpatients with cirrhosis, bCr was ≤0.70, 0.70‐0.97, and ≥0.97 mg/dL in 28%, 38%, and 34%, respectively. At a median follow‐up of 16 (range 8‐28) months, 143 (37%) had one or more AKI episode, which increased significantly by bCr group (24% versus 37% versus 48%, P  = 0.001). Of these 143 with AKI, 13% developed persistent kidney injury. A multivariable Cox regression analysis highlighted that bCr (hazard ratio [HR], 2.96) and ΔCr (HR, 2.05) were the only factors independently associated with the development of persistent kidney injury ( P  < 0.001). The likelihood of death/delisting increased by bCr group (14% versus 19% versus 28%, P  = 0.03). A competing risk analysis demonstrated that each 1 mg/dL increase in bCr was independently associated with a 62% higher risk of death/delisting when accounting for transplantation and adjusting for confounders. Conclusion: AKI is not only common in outpatients with cirrhosis but even "clinically normal" bCr levels significantly impact the risk of persistent kidney injury and waitlist mortality, supporting the need for a lower clinical threshold to initiate monitoring of renal function and implementation of kidney‐protective strategies.